Training And Assistance In Maintenance, Intensification, Rehabilitation Of Coffee Plant In Colol Village, Lamba Leda District, East Manggarai District - Umbu A Hamakonda; Igniosa Taus; Victoria Ayu Puspita; Silverius Betu; Victoria Coo Lea; Anastasia H P Enga; Maria Arnoldiana D Uran (BADAN PENERBIT STIEPARI PRESS, 2024)
Coffee is one of the dominant plantation crops in Colol Village, Lamba Leda District. Colol Village, Lamba Leda District, is one of the coffee development centers in East Manggarai Regency. The aim of this community service activity is to develop and develop farmers through the coffee commodity business in order to produce quality and reliable human resources. Reliable human resources will be able to manage all existing natural resource potential to produce quality coffee, both in terms of production and productivity, so as to create added value and competitiveness according to market needs. Apart from that, in the long term it is hoped that this activity will be able to increase the income of coffee farmers and create jobs as well as being able to increase the competitiveness of the coffee value chain by providing more business opportunities in the coffee plantation subsector. East Manggarai Regency, especially Colol Village, Lamba Leda District. The focus of implementing this service is increasing the knowledge and skills capacity of farmers in managing coffee plants through maintenance, intensification and rehabilitation to improve the quality of the harvest. Through training and mentoring activities, coffee farmers are able to carry out coffee maintenance, intensification and rehabilitation.